CONTRIBUTION TO THE IMPROVEMENT OF THE FARMING PRATICES OF PRODUCTION OF PINEAPPLE IN BENIN: CASE OF THE MUNICIPALITY OF ALADA IN THE DEPARTMENT OF THE ATLANTIC - Batamoussi, Michel Hermann; Xavier, Bachabi S. François; Tokore, Joseph Sabi Bira Orou Mere; Babayai O., Loukmane Laleye; Tovihoudji, Pierre G. (European Scientific Journal, ESJ, 2015)
In Benin, pineapple is an important fruit crop, mainly grown in the Atlantic department. The survey in prospect to improve the production practices of pineapple in Benin took place in the municipality of Allada, in the Department of Atlantic. The objective aimed by the survey is to check off the different convenient in use by the pineapple’s producers in the municipality and to make a comparative analysis of it with the scientifically advisable practices, to propose to the producers the necessary practices. To reach this objective, we used the semi-structured interview and the interview structured to collect the information, the synthesis of suitable literatures for comparison. Results indicated that the production practices were very diverse, especially regarding planting material used (slips, hapas and suckers), planting density, flowering induction, and fertilizer application. The results revealed that the application level of the technical itineraries for the production of pineapple in the municipality is weak. Indeed, the certified dismissals don’t exist in Allada. All producers tell to appropriate the dismissals on their own harvests or buy them by the neighbors. Although uncertified, the dismissals are not treated before their setting in earth. Fertilization is done without previous survey of soil and without leaf diagnosis. The organic manure is not quite of the practiced and the specific manure (NPK-S-Mg) is not of use because inaccessible. With regard to the ploughing, it is flatbed but only 40% of the producers respect the depths of advisable ploughing (30-35cm). Tackling all these constraints would help producers improve the quantity and quality of produced pineapple in this municipality.